Critical reflections on the contribution to democratic deliberation of a typical conversational rhizome on twitter: a case study of Professor Jonathan Moyo’s selected tweets. - Guvakuva, Shyline Sharone (Midlands State University, 2018)
The researcher focused on the contribution to democratic deliberation of a typical rhizome on twitter. The study explored the deliberations that were taking place on Jonathan Moyo’s twitter page @ProJNMoyo’s selected tweets. The researcher used the public sphere theory with close reference to the virtual public sphere, the network society theory as well as the deliberative democracy theory. The theories helped the researcher by setting the aggregates on how to give evaluations and judgements to the selected tweets in order for her to come up with well informed and guided findings. The researcher used qualitative research and also made use of purposive sampling as well as convenience sampling. The research also analysed data using critical discourse analysis as well as hermeneutics of interpretation. The data was then presented in thematic and narrative approaches .The study revealed that twitter is rhizomatic and that it is through its rhizomatic nature that democratic deliberations are made possible .The rhizomatic nature of twitter also showed that twitter deliberations are not just clickitivism .The study also revealed that twitter usage in Zimbabwe is mainly centralised to those who are financially stable.